1999
DOI: 10.1038/sj.bjp.0702708
|View full text |Cite
|
Sign up to set email alerts
|

A771726, the active metabolite of leflunomide, directly inhibits the activity of cyclo‐oxygenase‐2 in vitro and in vivo in a substrate‐sensitive manner

Abstract: 1 The immunosuppressive and anti-in¯ammatory drug le¯unomide has several sites of action, although its precise mode of action is unknown. 2 Here we show in vitro and in vivo that le¯unomide and/or its active metabolite A771726, inhibit the activity of cyclo-oxygenase (COX) at doses below those that a ect protein expression. 3 In J774.2 macrophages treated with endotoxin for 24 h to induce COX-2 and iNOS, le¯unomide and A771726 inhibited more potently the accumulation of PGE 2 (A771726, IC 50 3.5 mg ml 71 ) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 27 publications
3
42
0
4
Order By: Relevance
“…It was proposed that JNK had a pathological role in AILI in part by contributing to mitochondrial injury [14,21,35]. Potential limitations of these studies, as acknowledged by the investigators [21,22] is that JNK inhibitors may not be specific and as reported can affect other signaling events that could lead to the misinterpretation of results [36][37][38][39]. Further, some of the JNK inhibitors were dissolved in vehicles containing DMSO [14,21] and polyethylene glycol [22,35], which may affect various parameters at the cellular and molecular level [34,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that JNK had a pathological role in AILI in part by contributing to mitochondrial injury [14,21,35]. Potential limitations of these studies, as acknowledged by the investigators [21,22] is that JNK inhibitors may not be specific and as reported can affect other signaling events that could lead to the misinterpretation of results [36][37][38][39]. Further, some of the JNK inhibitors were dissolved in vehicles containing DMSO [14,21] and polyethylene glycol [22,35], which may affect various parameters at the cellular and molecular level [34,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated as an effective inhibitor of PDGF-mediated signal transduction and tumor growth [56] and as an EGF receptor inhibitor [57]. Leflunomide/SU101 yields an active metabolite (SU0020 or A771726), that inhibits COX-2 activity in vitro [58]. SU101 was well tolerated in a Phase I study in cancer patients, when administered as a 24-hour continuous i.v.…”
Section: Tyrosine Kinase Inhibitors Of the Pdgf Family (Pdgf Receptormentioning
confidence: 99%
“…In addition, the COX-2 inhibition was reversed by high levels of arachidonic acid. 46 These two aspects suggest that any meaningful clinical effects of COX-2 inhibition by teriflunomide are limited.…”
Section: Other Effectsmentioning
confidence: 99%